The currency of politics the political theory of money from Aristotle to Keynes - Eich, Stefan, 1983- (Princeton University Press, 2022)
"The financial crisis of 2008 prompted a renewed critical interest in the moral limits and the sense of justice inherent in the market economy. But while the valuable pursuits of political theorists have enabled them to speak more directly to the economic dimension of our lives, they only rarely touch on the political roots of the central institution of all market economies-money. In The Currency of Politics, political theorist Stefan Eich responds to this blind-spot by offering an intellectual history of money, as the concept was developed over time through the insight of some key political philosophers. Showing the ways in which money is an inherently political institution, Eich examines six key moments of monetary crisis and the political reflection they elicited, from Aristotle and the invention of coinage to the "Great Inflation" of the 1970s and the subsequent disappearance of discussions of money from political theory. What ties the moments together, he argues, is a set of recurring concerns with monetary politics that unfold as a conversation across time, constantly offering revisionist assessments of prior crises. Whether we know it or not, these layers of crisis have come to define the way we look at money, and they continue to reverberate today. In surveying the history Eich responds to the most pressing political questions about money which arise from within the long history of political thought and maps out several possible paths for thinking politically about the governance of money"--